Optimization of virtual design and machining time of the mold master ceramic jewelry products with Indonesian batik motifs - Bawono, B.; Yuniarto, T.; Sanusi, C. E. P.; Felasari, S.; Widyanarka, O. K. W.; Anggoro, P. W. (Frontiers in Mechanical Engineering, 2024)
Batik has been the cultural heritage of the Indonesian nation since the 17 th century. On October 2, 2009, the United Nations Educational, Scientific, and Cultural Organization (UNESCO) designated Batik as part of Indonesia's traditional clothing as Indonesia's cultural heritage. This research proves that Batik is an attractive and artistic ornament of ceramic jewelry products. This ornament can increase the selling value and storytelling of the product. Naruna is a local handmade porcelain ceramic factory in Indonesia with excellence in unique colored tableware and consistently trying to develop new designs in ceramic jewelry. Modern technology in computer-based virtual design and machining on dining plate tableware with the Batik Kawung motif is also applied in this paper to obtain a master design for ceramic jewelry prints. The design stage begins with selecting ornament patterns with creative methods to form a 3D CAD model of ceramic jewelry using artistic Art CAM. The optimization of computer-aided manufacturing-based to obtain machining strategy using the software. The software is Autodesk Power Mill, whose NC Code can be directly manufactured on a CNC router machine. This combination can speed up the production process time to meet the production capacity at Naruna and get detailed, accurate, precise, and consistent textures and ornaments, thereby meeting NCS consumer demand for ceramic jewelry products. The simulation results of the two master print patterns are 141 hours, 56 minutes, and 46 seconds; the machining time is estimated at 153 hours. This research saves about 11 hours of time processing. The resulting NC Code can be appropriately processed on a CNC router machine with a Mach 3 post-processor.